ANALYSIS OF WORK MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE WORK PRODUCTIVITY AT CV. MGS TANJUNG HAPPY - Siti Natasya Alfadiah; Muhammad Yalzamul Insan; Fitra Arlina Nasution (RADJA PUBLIKA, 2024)
This research was conducted at CV. MGS Tanjung Selamat with the aim of analyzing the influence of work motivation and work environment partially and simultaneously on employee work productivity. The population is 37 employees who work in the company with a random sample, namely a saturated sample so that the total sample is 37 respondents. The type of data used is primary data and the data sources used are secondary data, data collection techniques use literature studies, surveys and observations. Data analysis techniques are multiple linear regression, classical assumption testing and hypothesis testing. The research results show that work motivation and work environment partially and simultaneously have a positive and significant effect on employee work productivity. There is a very strong correlation between work motivation and work environment and employee work productivity. Employee work productivity in the company can be explained by work motivation and work environment by 66.6% and the remaining 33.40% can be explained by other variables not studied, such as incentives, training, career development and so on.